Application of passive-acoustic telemetry to explore the behaviour of ballan wrasse (Labrus bergylta) and lumpfish (Cyclopterus lumpus) in commercial Scottish salmon sea-pens - Leclercq, Eric; Zerafa, Benjamin; Brooker, Adam J; Davie, Andrew; Migaud, Hervé (Aquaculture, 2018)
A passive-acoustic telemetry system was used for the first time for the fine-scale, three-dimensional tracking of individual cleaner fish in commercial Scottish salmon sea-pens in full commercial operation. The aim was to test the system performance and provide baseline data on the comparative distribution and swimming activity of individual ballan wrasse and lumpfish under standard farm practices with the long-term aim of informing stocking and husbandry strategies. In March 2015, wild ballan wrasse (Labrus bergylta) (115 ± 20 g; n = 13) and farmed lumpfish (Cyclopterus lumpus) (281 ± 42 g; n = 13) previously deployed in June–October 2014 were recaptured, implanted with acoustic tags pinging every 6–12 s and released into their original sea cage holding Atlantic salmon (Q2 2014; 2059 ± 35 g mean-weight). Control tags were deployed in cleaner fish hides to validate the system performance. Positional data from nine specimens per species were analysed from March 24th to June 1st 2015, during which time water temperature rose from 7.2 to 9.1 °C and water salinity averaged 26.8 ± 1.5 ppt at 4 m depth. The accuracy of the acoustic positions averaged 0.6 m across the three dimensions of all control tags and was < 1 m in 93% of all cases. Significant differences in the distribution and activity of ballan wrasse and lumpfish were observed. Ballan wrasses spent 60 ± 2% of the day-time at or below 15 m, were positioned at significantly shallower depths at night and seldom used the hides provided despite an apparent resting behaviour at the pen bottom and corners. In comparison, lumpfish spent over 80% of the time above 10 m, used hides extensively and preferentially at night (50.1 ± 2.1% at night), but to a lesser extent when the water temperature increased. The acoustic tracking system proved to be an effective tool for visualising cleaner fish behaviour under challenging farm conditions, and the study highlights the critical role of hides in cleaner fish husbandry. Overall, the study quantified species-specific ...